At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
[tex]a_n = 23 +12(n -1)[/tex]
Explanation:
The [tex]n[/tex]th term of an arithmetic sequence is explicitly defined as [tex]a_n = a_1 +d(n -1)[/tex] where [tex]a_1[/tex] is the first term of the sequence and [tex]d[/tex] is the the common difference.
From the given first five terms of the sequence we can see that the first term is [tex]23[/tex] so [tex]a_1 = 23[/tex].
The common difference, [tex]d[/tex], can be calculated by [tex]a_n - a_{n -1}[/tex] so we'll find the common difference of the given sequence by letting [tex]n = 2[/tex]
[tex]d = a_2 - a_{2 -1} \\d = a_2 -a_{1} \\d = 35 -23 \\ d = 12[/tex].
Now let's plug everything we know.
[tex]a_1 = 23[/tex]
[tex]d = 12[/tex]
[tex]a_n = 23 + 12(n -1)[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.